Secondary infections and diseases associated with Varroa jacobsoni - Ball B.V. (The varroosis in the Mediterranean region, 1997)
The parasitic mite Varroa jacobsoni may directly and indirectly affect the type and prevalence of honey bee pathogens causing mortality in infested colonies. An increase in the incidence of chalkbrood (Ascosphaera apis) is probably the result of inadequate brood care due to a depletion of the adult bee population for other reasons. Laboratory studies have shown that the mite is capable of causing septicaemic infection by introducing bacteria contaminating the body surface of honey bee pupae into the haemolymph and it is capable of transmitting infection to healthy pupae during feeding. However, in nature the primary cause of adult bee and brood mortality in severely infested colonies is honey bee virus infections which the mite may first activate to multiply and then transmit. A better understanding of host-parasite-pathogen interactions should provide options for the development of improved control strategies by the better targeting and timing of treatments.
Seminar on The Varroosis in the Mediterranean Region, 1996/09/22-23, Granada (Spain)